Efficacy and Safety of Insulin Icodec Versus Glargine U100- A meta-analysis of randomized controlled trials - Zerihun, Kirubel (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.